Design of a Herringbone-Grooved Bearing for Application in an Electrically Driven Air Compressor - Henning Schlums; Christian Hühne; Michael Sinapius (Machines, 2022)
A turbo compressor was investigated to ensure the operational reliability of the charging of fuel cell systems. This study investigated air-lubricated herringbone bearings to support the high-speed rotating shaft. For reliable operation of the rotor bearing system, stable operation in the whole speed range (up to 120 krpm), as well as low lift-off speed, is an important issue. Some publications containing guidelines for an optimized design in terms of stability and lift-off behavior date back to the 1970s, with some simplifying assumptions (such as narrow groove theory and small eccentricity analysis). Many publications have addressed the calculations, as well as the optimization of herringbone-grooved bearings; however, general design guidelines are still missing in the view of the authors. Although the investigations related to bearings for the support of a lightweight rotor for a special compressor of a fuel cell unit, this study could also indicate favorable bearing designs for other high-speed applications. Here, the compressible Reynolds equation was solved in the whole solution domain using a conservative finite difference scheme, and the corresponding bearing characteristics were determined. In a perturbation analysis, the linearized dynamic coefficients of the herringbone bearing are calculated. To compare the suitability and performance of the various herringbone-grooved bearing designs, especially at high speed, the simple model of a Jeffcott rotor airborne with two identical herringbone-grooved journal bearings (HGJBs) was used. The geometrical parameters of the HGJBs were varied, and their effects on bearing characteristics and stability were evaluated. Recommendations concerning favorable geometrical bearing parameters for a sufficiently high stability threshold speed and reasonable low lift-off speed were the result of the parameter study.